The Length of Days : An Urban Ballad - Rafeyenko, Volodymyr (Harvard University Press, 2023)
In The Length of Days, featuring a wild cast of characters, Rafeyenko combines poetry and wicked humor with elements of magical realism. The novel is set in 2014, mostly in the composite Donbas city of Z--an uncanny foretelling of what this letter has come to symbolize since February 2022, when Russia launched a full-scale invasion of Ukraine.
Keywords: Russo-Ukrainian War, 2014- -- Fiction.; Magic realism (Literature); Donets Basin (Ukraine and Russia) -- Fiction.; Guerre russo-ukrainienne, 2014- -- Romans, nouvelles, etc.; Réalisme magique (Littérature); Donbass (Ukraine et Russie) -- Romans, nouvelles, etc.; LITERARY CRITICISM / General.; Europe -- Donets Basin; Since 2014; Electronic books.; Fiction